Longitudinal Trajectories of Sedentary Time and Physical Activity in Children With Cerebral Palsy: Time to Move - Ineke Verreydt; Olaf Verschuren; Marieke De Craemer; Lauraine Staut; Daisy Rymen; Els Ortibus; Kaat Desloovere; Anja Van Campenhout (Journal of Physical Activity and Health, 2026)
Background : Children with cerebral palsy (CP) have reduced movement abilities, limiting physical activity (PA) and increasing sedentary behavior. No study so far applied a longitudinal design to examine changes in sedentary behavior and different levels of PA in relation to increasing age. Methods : Forty-five ambulant children with spastic CP, aged 2–11 years, participated in this longitudinal study, totaling 108 assessments (2–4 assessments/child). PA and sedentary behavior were measured using ActiGraph wGT3X-BT triaxial accelerometers, placed on the right hip. Linear mixed-effects models fitted effect of age on sedentary time and PA, for the total sample and Gross Motor Function Classification System (GMFCS) subgroups. Results were compared with cross-sectional data of 49 typically developing peers including data on sleep problems. Results : Based on linear mixed-effects models, sedentary time increased with 0.79%/year ( P = .0094), light PA decreased with 1.17%/year ( P < .0001), and moderate-to-vigorous PA increased with 0.33%/year ( P = .0003) in the total sample of children with CP. Children with GMFCS levels II/III presented with more sedentary time and less PA than children with GMFCS I, already at the age of 2 years old. Significant lower levels of light and moderate-to-vigorous PA, more sedentary time, and more sleep problems ( P < .05) were seen for the CP compared with the typically developing group. Conclusions : The unique longitudinal results indicate that with increasing age, light PA decreases, along with a greater increase in sedentary time compared with moderate-to-vigorous PA. The variability in individual trajectories highlights the importance of patient-tailored advice to optimize how children with CP spend their waking hours, especially with increasing age.